The Anatomical Distribution of Plasma Fibrinolytic Activity in Man During Cardiac Catheterisation - Gough, S C L; Smyllie, J; Sheldon, T; Rice, P J S; Grant, P J (Thrombosis and Haemostasis, 1992)
Regional circulating plasma levels of fibrinolytic activity were assessed in 15 patients undergoing cardiac catheterisation. The euglobulin clot lysis time (ECLT) was longer in the abdominal aorta (AA) than the inferior vena cava (IVC), (median difference – 17.5 min, p = 0.008). This was associated with higher inhibition of plasminogen activator activity (PAI) in the AA than IVC, – 1.75 IU/ml, p = 0.002. In the venous circulation the ECLT was higher in the peripheral venous sample than in the IVC, –25.5 min, p = 0.003, with higher PAI peripherally than in the IVC, -1.9 IU/ml, p = 0.001. There were no differences in ECLT, PAI, PAI-l:Ag or t-PA:Ag throughout the arterial circulation. These results demonstrate higher fibrinolytic activity with lower inhibitor activity in the venous compared to the arterial circulation. Within the venous circulation fibrinolytic activity is lower peripherally with increased inhibitor activity.